Cognitive Load Effects of AI Tutoring Systems Compared to Traditional Instructional Methods - Liu, Yuxin (International Journal of Social Sciences and English Literature, 2025)
The rapid integration of Artificial Intelligence (AI) in educational settings has transformed pedagogical approaches, with Intelligent Tutoring Systems (ITS) emerging as a prominent alternative to traditional instructional methods. This study examines the cognitive load effects of AI tutoring systems compared to conventional classroom instruction through the lens of Cognitive Load Theory (CLT). The research synthesizes recent empirical evidence to evaluate how AI-powered adaptive learning platforms manage intrinsic, extraneous, and germane cognitive load differently than traditional teacher-led instruction. Findings indicate that AI tutoring systems can effectively reduce extraneous cognitive load through personalized content delivery and real-time adaptations while maintaining optimal levels of germane load for knowledge construction. However, the effectiveness varies significantly based on implementation quality, subject domain, learner characteristics, and the integration of pedagogical principles. Traditional instructional methods demonstrate advantages in fostering social interaction and metacognitive development, though they may impose higher extraneous load on diverse learner populations. The study reveals that hybrid approaches combining AI tutoring with human instruction yield superior outcomes in managing cognitive load across different learning contexts. These findings have important implications for educational technology design and instructional practice, suggesting that AI tutoring systems should complement rather than replace traditional teaching methods to optimize cognitive resource allocation and enhance learning efficacy.